Analisis User Experience Pada Website Universitas Teknologi Sumbawa Menggunakan Metode Webqual - W, Yunanri; Susanto, Eri Sasmita; Yuliadi, Yuliadi; Zaen, Muhammad Taufan Asri; Oper, Nabila (Building of Informatics, Technology and Science (BITS), 2022)
Sumbawa University of Technology (UTS) is one of the educational institutions that utilize website technology in educational institutions. The Sumbawa University of Technology website, it can make it easier for the public to get information. User experience analysis on the Sumbawa University of Technology website to be able to find out the usefulness of the product or UX display that is applied in serving users. The purpose of this research is that the Sumbawa University of Technology website can make it easier for the UTS campus community and the public to get the important and latest information from the Sumbawa Technological University, and the campus can also know how users respond to the content or appearance of the UTS website. From the results of the questionnaire that has been conducted by researchers, more respondents chose "Neutral" and "Agree", because the response was good, there was no change in the UX appearance